The Effect Of Maternity Position On The Length Of Labor Time During The Active Phase Of Primigravida - Sri Wulan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Normal delivery is the process of fetal discharge and ari-ari in mothers with full-term pregnancy at the time of delivery, the mother needs special support in determining the position of labor because she has not had previous experience, especially in primigravida mothers. The choice of labor position is very important for the mother because the position can provide comfort and can facilitate the progress of labor. The purpose of this study was to determine the influence of both variables, namely the position of labor and the length of labor. Observational analytical research method with post test approach with design two experiments, a sample of 26 people consisting of 2 groups, 13 people in squatting and standing position groups and 13 people sitting middle position and left tilt with accidental sampling techniques, research in RB Cahaya 2 Lubuk Pakam, data collection using partograph sheets, data results tested with Simple t test. The results showed that there was an influence of Maternity Position on the length of labor time during the active phase of Primigravida with a p-value 0,00. It is recommended to all mothers who give birth to be able to choose the right position so that labor can take place smoothly and it is also recommended to husbands and health workers to support the positions of mothers who will give birth.